2014
DOI: 10.1002/pssc.201300477
|View full text |Cite
|
Sign up to set email alerts
|

Excellent uniformity on large diameter GaN on silicon LED wafer

Abstract: We report on the crystal quality and on‐wafer device performance of GaN‐on‐Si LED wafers grown by metalorganic chemical vapour deposition on Si(111) substrates. Average XRD FWHM of 343 arcsec and 456 arcsec for the 002 and 102 reflections, respectively, are measured for GaN‐on‐Si template wafers and a dislocation density around 5×108 cm–2 is determined via etch pit density. Excellent electroluminescence uniformity for the 150 and 200 mm blue LED wafers was achieved. The standard deviation values measured acros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…There are few reports about the uniformity of the crystal quality of the GaN epitaxial layer on the Si substrate. In 2014, Pinos et al [26] reported the coefficient of variation of the 9.1% GaN (0002) XRD rocking curve FWHM on a 6-inch Si substrate. In 2017, Ji et al [27] reported a 2.4% coefficient of variation of epitaxial wafers of the same size.…”
Section: Introductionmentioning
confidence: 99%
“…There are few reports about the uniformity of the crystal quality of the GaN epitaxial layer on the Si substrate. In 2014, Pinos et al [26] reported the coefficient of variation of the 9.1% GaN (0002) XRD rocking curve FWHM on a 6-inch Si substrate. In 2017, Ji et al [27] reported a 2.4% coefficient of variation of epitaxial wafers of the same size.…”
Section: Introductionmentioning
confidence: 99%